2017
DOI: 10.1016/j.enconman.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of loop heat pipes with smooth and rough porous copper fiber sintered sheets

Abstract: Smooth and rough porous copper fiber sintered sheets, employed here as wicks for loop heat pipes for the first time, were fabricated using a low-temperature solid-phase sintering method. The capillary performance of these porous copper fiber sintered sheets were analyzed and discussed. The influence of the surface morphology, filling ratio, and working fluid on the thermal resistance, evaporator wall temperature, and start-up time of the loop heat pipes were investigated. The results showed that the capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Whereas the wetting angle between copper and carbon, even at 1000 °C, copper and graphite still exist a wetting angle of 140°As shown in figure 4, the copper fibers are only mechanically bonded to the carbon matrix [24]. Thus, there is a sidewall spacer between the copper fibers and the carbon matrix, where cracks are most likely to occur and expand during compression [25]. Moreover, it is found that if the content of copper fiber is reasonably controlled (about 5 wt%), the influence of copper fibers on compressive strength will be minimized.…”
Section: Mechanical and Electrical Propertiesmentioning
confidence: 99%
“…Whereas the wetting angle between copper and carbon, even at 1000 °C, copper and graphite still exist a wetting angle of 140°As shown in figure 4, the copper fibers are only mechanically bonded to the carbon matrix [24]. Thus, there is a sidewall spacer between the copper fibers and the carbon matrix, where cracks are most likely to occur and expand during compression [25]. Moreover, it is found that if the content of copper fiber is reasonably controlled (about 5 wt%), the influence of copper fibers on compressive strength will be minimized.…”
Section: Mechanical and Electrical Propertiesmentioning
confidence: 99%
“…Ding et al [37] mainly studied the filling ratio and Freon types as the influence factors of the loop HP system used in data centre cooling and analysed the relationship between the heat transfer capacity and filling ratio varying from Freon types. Ling et al [38] for the first time, applied smooth and rough porous copper fiber sintered sheets into a loop HP system. They investigated the influence of filling ratio, highlighting that a filling ratio at 30% of the deionized water was the optimal combination for their designed loop HP.…”
Section: Filling Ratio Of the Working Fluidmentioning
confidence: 99%
“…The capillary wick, which provides the driving force to facilitate liquid flow from the condenser to the evaporator and further maintain vapor–liquid phase-change circulation, is one of the vital components of the vapor chamber. The traditional metal mesh wick, , sintered wick, , and composite wick are not insulators and cannot satisfy the insulation requirements of high-voltage electronic components . Although the sintered porous ceramic wick and glass wick are insulators, their extremely low thermal conductivity, high cost for sintering the wicks onto the shell plate, and the presence of contact thermal resistance at the interface of the wick and the shell plate limit their widespread use for ceramic vapor chambers.…”
Section: Introductionmentioning
confidence: 99%